Forests and forestry in Small Island Developing States. (1st December 2002) - Wilkie, M. L.; Eckelmann, C. M.; Laverdière, M.; Mathias, A.
While the combined forest cover of Small Island Developing States (SIDS) is insignificant in global terms, forests and trees on these islands are extremely important for the wellbeing of the inhabitants. For most of the larger islands, forests also contribute significantly to the national economy and to international trade in wood and non-wood forest products. In addition, forest resources on several islands are of global importance in terms of their role in the conservation of biological diversity, in particular endemic species and genetic variability. As a group, SIDS are well endowed with forests but the extent of forest cover varies greatly among island states. Despite variations in size, location, population density and climatic, geological and topographic conditions, these states share many characteristics which impose particular constraints, but also some which offer unique opportunities, for the sustainable management of their forests and trees.